Surgical and Oncological Outcomes of Minimally Invasive Left Pancreatectomy for Pancreatic Cancer: Robotic vs. Laparoscopic Approach - Matteo De Pastena; Gabriella Lionetto; Salvatore Paiella; Martina Maruccio; Federico Faustini; Elisa Venturini; Antonio Pea; Fabio Casciani; Giuseppe Malleo; Alessandro Esposito (Current Oncology)
Objective: This study compares the surgical and oncological outcomes of minimally invasive robotic (RLP) and laparoscopic (LLP) left pancreatectomy in pancreatic cancer (PC) patients. Methods: Data from patients who underwent minimally invasive left pancreatectomy between 2013 and 2023 were analyzed. Two groups were identified: RLP and LLP. Perioperative outcomes were compared, including operative time, blood loss, conversion rate, and postoperative complications. Oncological outcomes included margin status, lymph node retrieval, lymph node status, overall survival (OS), and disease-free survival (DFS). Results: Fifty-four patients were divided into the LLP (n = 39) and RLP (n = 15) groups. The median operative time was shorter for LLP than RLP [260 min vs. 366 min, p = 0.007]. Blood loss and conversion rates were comparable (p > 0.05). In the LLP group, significantly more lymph nodes were harvested (29 vs. 19, p = 0.05), and a higher percentage of positive lymph nodes was noted (72% vs. 40%, p = 0.033). No significant difference was found in the R0 resection status (82% vs. 73%, p = 0.358). After a median follow-up of 26 months, OS (23 months vs. 34 months, p = 0.812) and DFS (17 months vs. 16 months, p = 0.635) were similar. Conclusion: RLP provides outcomes identical to LLP in treating body–tail pancreatic cancer, with further studies needed to confirm its long-term oncological efficacy.